Кредитна та депозитна поведінка домогосподарств в україні як складова забезпечення їх фінансової стійкості - Качула, Світлана Валентинівна; Kachula, Svitlana; Лисяк, Л. В.; Lysiak, L. (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2023)
У статті здійснено аналіз депозитної та кредитної поведінки домогосподарств в економічній системі України якскладової підтримки їх фінансової стійкості домогосподарств та окреслено заходи щодо зміцнення останньої. Окреслено характерні особливості депозитної поведінки домогосподарств. Показані основні аспекти реалізації кредитно-депозитної політики банківськими установами, проведено окремий аналіз депозитної та кредитної поведінки домогосподарств за період з 2011 р. по 2022 р. та за п'ять місяців 2023 р., який показав, що з 2019 р. Домогосподарства обирають вкладення своїх коштів "на вимогу", адже зазвичай даний тип вкладення коштів дозволяє зняти їх з рахункув будь-який час, не втрачаючи відсотків. Частка ж депозитів "до 1 року", "від 1 до 2 років" та "більше 2 років" стрімко знижується. Так, впродовж 2011—2022 рр. частка депозитів до 1 року зменшилась майже на 11%; від 1 до 2 років — на28,5%; більше 2 років — 7,8%. Аналіз наданих споживчих кредитів домашнім господарствам впродовж 2011-2022 рр. та за 5 місяців 2023 р. по-казав, що найбільш затребувані кредити строком "до 1 року", їх частка за аналізований період збільшилась майже на 33% і в 2023 р. продовжує зростати. Зазначено, що ключовими елементами для підтримки фінансової стійкості домогосподарств є їх раціональна депозитна та кредитна поведінка, активне управління коштами та фінансове плануван-ня, фінансова та комп'ютерна освіченість/грамотність. Зроблено висновок, що надання домогосподарствам знаньщодо вмілого використання інструментів фінансового планування та достовірного і відповідального консультування з управління власними та кредитними коштами може допомогти їм впоратися з фінансовим стресом і змінити/згладити негативні ситуації та виробити оптимальну кредитну та/або депозитну поведінку, що дозволить досягти заінших рівних умов фінансової стабільності. The article examines the role of households in the economic system of Ukraine and the relationship between the financial stability of households, the banking system and the country as a whole. The goals of ensuring the balance of households, which allow to ensure stability of the financial situation of individual families, are considered. It has been established that during crises (the COVID-19 pandemic and Russia's invasion of Ukraine), the level of uncertainty increases, which directly affects the financial stability of households. Among the ways of overcoming crisis situations by households and stabilizing their financial situation, the implementation of the bank's credit and deposit policy and the implementation of digitalization of banking services are considered. In order to establish the effectiveness of credit and deposit policy by banking institutions, a separate analysis of deposit and credit behavior of households was conducted. The impact of credit and deposit behavior of households on their financial stability is proven. The analysis showed that household deposit behavior reflects actions and decisions regarding saving and investing money in deposit accounts in banks and other financial institutions. The volume of household deposits attracted by banks of Ukraine in 2011-2022 and for five months of 2023 showed that, starting from 2019, households choose to deposit their funds on demand, as this type of deposit allows them to be withdrawn from the account at any time without losing interest. The share of deposits "up to1 year", "from 1 year to 2 years" and "more than 2 years" is rapidly decreasing. Thus, in 2022, the share of deposits up to1 year has decreased by almost 11% since 2011; from 1 year to 2 years — 28.5%; more than 2 years — 7.8%. The conditions of reduction of real incomes and slowdown of wage growth may affect the financial stability of households. A bank loan can become one of the tools that households use to support their expenses in conditions of reduced income or increased expenses. The analysis of loans granted to households by target direction and repayment terms in 2011-2022 and for 5months of 2023 showed that the largest share of consumer loans with a term of "up to 1 year". From 2011 to 2022, it increased by almost 33% and will continue to grow in 2023. The share of consumer loans from 1 year to 5 years for the analyzed period remains almost unchanged, but more than 5 years decreased by 32%. It is noted that the key elements for maintaining the financial stability of households are their rational deposit and credit behavior, active management offunds and financial planning, financial and IT education/literacy. It was concluded that providing households with knowledge on the skillful use of financial planning tools and reliable and responsible counseling on managing their own and credit funds can help them cope with financial stress and change/smooth negative situations and develop optimal credit and/or deposit behavior that will allow to achieve financial stability when everything else is equal.
Credit and deposit behavio r of households in ukraineas a c omponent o f ensuring their financial stability
Keywords: домогосподарство; household; фінансова стійкість; financial sustainability; цифрові інструменти; digital tools; банківський кредит; bank credit; кредитна поведінка домогосподарств; household credit behavior; депозитна поведінка домогосподарств; household deposit behavior; фінансовий ризик; financial risk; фінансове планування; financial planning; фінансова та комп'ютерна грамотність; financial and computer literacy